The effect of obstructive sleep apnea on the cardiovascular system - Wijata, Aleksandra; Wydeheft, Lidia; Janiak, Michał; Fronc, Kamila; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2022)
Introduction: Obstructive Sleep Apnea is a disease entity that affects many aspects of life, but is often overlooked and underdiagnosed. OSA is defined as episodes of apnea-hypopnea that disturbs not only sleep, but also daytime functioning. Symptoms can be divided into night symptoms (not breathing, snoring, gasping, fragmented sleep) and daytime symptoms (fatigue, low concentration, morning headaches, decreased libido). Moreover, OSA through many mechanisms affects the cardiovascular system and leads to its dysfunction. Purpose: The aim of this study is to draw attention to the often underdiagnosed disease entity, which is OSA, which, if left untreated, may lead to serious complications. Material and methods: In 2022, the PubMed and Google Scholar databases were searched using the following keywords: OSA, apnea, cardiovascular disorders, arrhythmias and heart disease. Works in English with the most recent data have been selected. Summary: OSA is strongly associated with cardiovascular disorders, moreover, in both cases, we find similar risk factors for these disorders. A correlation has been demonstrated between OSA and atrial fibrillation, hypertension, and arrhythmias. On the other hand, OSA is still underdiagnosed and more research is needed to understand the correlation between these diseases.